2002
DOI: 10.1002/gcc.10033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel fusion partners of ALK, the anaplastic lymphoma kinase, in anaplastic large‐cell lymphoma and inflammatory myofibroblastic tumor

Abstract: ALK-positive anaplastic large-cell lymphoma (ALCL) has been recognized as a distinct type of lymphoma in the heterogeneous group of T/Null-ALCL. While most of the ALK-positive ALCL (ALKomas) are characterized by the presence of the NPM-ALK fusion protein, the product of the t(2;5)(p23;q35), 10-20% of ALKomas contain variant ALK fusions, including ATIC-ALK, TFG-ALK, CLTC-ALK (previously designated CLTCL-ALK), TMP3-ALK, and MSN-ALK. TMP3-ALK and TMP4-ALK fusions also have been detected in inflammatory myofibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(184 citation statements)
references
References 40 publications
6
176
0
2
Order By: Relevance
“…Aberrant ALK expression has been described in anaplastic large-cell lymphomas and inflammatory myofibroblastic tumors and results from genomic rearrangements of the ALK gene with various partner genes. [48][49][50][51] ALK expression in DLBCL is not the result of full-length ALK expression as originally reported 52 but is due, in most of the cases, to a recurrent translocation t(2;17)(p23;q23) resulting in the CLTC-ALK fusion protein. 43,44 In a few cases ALK expression in these tumors can also result from the t(2;5)(p23;q35) translocation leading to the NPM (nucleophosmin)-ALK fusion protein.…”
Section: Alk þ Dlbclmentioning
confidence: 63%
“…Aberrant ALK expression has been described in anaplastic large-cell lymphomas and inflammatory myofibroblastic tumors and results from genomic rearrangements of the ALK gene with various partner genes. [48][49][50][51] ALK expression in DLBCL is not the result of full-length ALK expression as originally reported 52 but is due, in most of the cases, to a recurrent translocation t(2;17)(p23;q23) resulting in the CLTC-ALK fusion protein. 43,44 In a few cases ALK expression in these tumors can also result from the t(2;5)(p23;q35) translocation leading to the NPM (nucleophosmin)-ALK fusion protein.…”
Section: Alk þ Dlbclmentioning
confidence: 63%
“…5 However, a number of recent studies have identified a growing list of alternative translocation partners (X-ALK) that appear also to activate ALK. [16][17][18][19][20][21][22] All of these are characterized by changes in the subcellular localization of ALK, being located either within the nucleus, nucleolus, and cytoplasm, restricted to the cytoplasm, or in the cytoplasmic membrane. Recognition of these variant translocations suggests that nuclear and nucleolar localization of ALK, as seen in cases with the t(2;5), is not critical to pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,9,[20][21][22][23][24][25][29][30][31][32] Cytogenetic and molecular analyses have demonstrated a number of ALK fusion gene partners, including RANBP2-ALK, TPM3-ALK, TPM4-ALK, CLTCALK, CARS-ALK and SEC31L1-ALK. 5,9,21,25,29,31 In the present study, ALK rearrangements were identified in 14 of 21 cases of inflammatory myofibroblastic tumor of the urinary bladder.…”
Section: Utility Of Alk-1 Protein Expressionmentioning
confidence: 99%